The Upper Semicontinuity of Random Attractors for Non-Autonomous Stochastic Plate Equations with Multiplicative Noise and Nonlinear Damping (Journal of Nonlinear Modeling and Analysis, 2024)
Based on the existence of pullback attractors for the non-autonomous stochastic plate equations with multiplicative noise and nonlinear damping defined in the entire space $\mathbb{R}^n$ by Xiaobin Yao in [15], in the paper, we further investigate the upper semicontinuity of pullback attractors for the problem.
Keywords: Upper semicontinuity; attractors; plate equation; unbounded domains; multiplicative white noise.